Inhibition of TLR4 Induces M2 Microglial Polarization and Provides Neuroprotection via the NLRP3 Inflammasome in Alzheimer’s Disease - Cui, Weigang; Sun, Chunli; Ma, Yuqi; Wang, Songtao; Wang, Xianwei; Zhang, Yinghua (Frontiers in Neuroscience, 2020)
Accumulating evidence indicated that activation of microglia and neuroinflammation reaction played a prominent role in Alzheimer's disease (AD). Inhibition of toll-like receptor 4 (TLR4) has been shown to be associated with immune responses and brain damage, but its effects on AD remain unclear. This study mainly aimed to investigate the protective effect of TAK-242 (TLR4 specific inhibitor) on the microglia polarization and neuroprotection in AD mouse model and the underlying mechanisms. We found that APP/PS1 transgenic AD mice exhibited a dramatic increase in TLR4 levels concomitant with a significantly higher expression of inflammatory microglia in contrast to C57BL/6 wild type mice. Furthermore, inhibiton of TLR4 by TAK-242 administration significantly improved neurological function, decreased the level of Bax and caused a significant reduction in the levels of M1-markers (iNOS and TNFα), while the expressions of M2-phenotype markers (Trem-2 and Arg-1) were increased both in vivo and in vitro. Furthermore, TAK-242 treatment enhanced BV2 microglial phagocytosis. Moreover, Aβ25-35 caused the upregulation of inflammatory cytokine production, MyD88, NF-kappaB-p65 and NLRP3, which could be ameliorated by NLRP3-siRNA or TAK-242, an inhibitor of TLR4. These findings indicated that TLR4 inhibition provided neuroprotection and promoted microglia switch from the inflammatory M1 phenotype to the protective M2 phenotype in AD. The mechanism may be related to modulation of the MyD88/NF-kappaB/NLRP3 signaling pathway.